Islamic social finance: a tool for development and economic Inclusion - Mohd. Zain, Nor Razinah; Engku Ali, Engku Rabiah Adawiah (Cambridge Institute of Islamic Finance, 2019)
The United Nations' Sustainable Development Goals (SDGs) are assertive statements of intent to achieve the long term well-being of people and planet. Beyond its religious foundation, Islamic social finance provides potential solutions in achieving SDGs. While, the seventeen (17) SDGs are interconnected to each other, the main focus can be found in the alleviation of poverty, democratic governance and peace building, mitigation of climate change and disaster risk, and balancing the economic inequality (UNDP, 2019). It is interesting to note that the SDGs are very much in line with the Shariah principles and its underlying philosophy better known as Maqasid Al-Shari'a. The role of Islamic social financing in connecting potential donors with humanitarian issues; effectively supports the SDGs if this sector is properly developed, managed and utilised with transparency, accountability, and efficiency.